(untitled) (Journal of Eye Movement Research, 2009)
Vergence eye movements are frequent in every day life and important for depth perception. Yet, studies of vergence in elderly are rare. We examined convergence and divergence between targets placed along median line at 20, 40 or 150cm. Thirteen elderly (70±11years) and ten young (25±3years) adults participated in the study. The gap paradigm (i.e., the fixed stimulus is extinguished prior to target onset) and the overlap paradigm (the fixed stimulus remains illuminated after target onset) were used to elicit reflexive or voluntary eye movements. Latency of convergence and divergence increased with age in both gap and overlap conditions. Both young subjects and elderly showed shorter latency of vergence under the gap condition than under the overlap condition. In the overlap condition, for elderly only, convergence resulted in longer latencies than divergence. In the gap condition express convergence was rare, while express latencies (80–120ms) were frequent for divergence starting from a near fixation point (at 20cm). The rates of express divergence were similar for young (23%) and elderly (21%). These results were in line with prior studies of saccades and indicated different aging effects on regular and express latencies.